Exploring social capital for family caregivers of patients with chronic organ failure: study protocol for a concept mapping study - Kai Chow Choi; Carmen Wing Han Chan; Marques Shek Nam Ng; Winnie Kwok Wei So; Wallace Chi Ho Chan; Helen Yue Lai Chan (BMJ Open)
Introduction Many family caregivers experience significant burdens, especially those who take care of patients with chronic organ failure. Although the social welfare system offers some material assistance, a more sustainable approach to supporting caregivers is warranted. This study aims to explore the social capital (ie, the internal strengths of a community that facilitate different social roles) available for these family caregivers.Methods and analysis A participatory design based on Trochim’s concept mapping framework will be used in this study. A total of 119 participants, including patients, family caregivers, professionals and other community members, will be recruited from the community. The study will be divided into three phases. In Phase I, qualitative methods will be used to prepare and generate statements. Participants will be asked to share their views on social capital for family caregivers through interviews. In Phase II, quantitative methods will be used to arrange these statements into a concept map, and participants will be asked to complete a questionnaire to prioritise the statements. Statistical methods will be used to create a map based on the responses. In Phase III, the concept map will be used to formulate action plans. The findings will be presented to the public to produce recommendations for social policy.Ethics and dissemination This study was approved by The Chinese University of Hong Kong Survey and Behavioural Research Ethics Committee (Reference No.: SBRE-20-714). Informed consent will be obtained from all participants. This study will reveal which forms of social capital can be mobilised to support family caregivers of patients with chronic organ failure. Recommendations on policies to improve the caregiving experience, strengthen social capital and enhance social care will be produced. Findings will be disseminated through academic conferences and journals, as well as local media to create a greater social impact.Trial registration number ChiCTR2100044171.